2014
DOI: 10.2967/jnumed.114.143180
|View full text |Cite
|
Sign up to set email alerts
|

Folate Receptor-β Imaging Using 99mTc-Folate to Explore Distribution of Polarized Macrophage Populations in Human Atherosclerotic Plaque

Abstract: In atherosclerotic plaques, the risk of rupture is increased at sites of macrophage accumulation. Activated macrophages express folate receptor-β (FR-β), which can be targeted by folate coupled to radioactive ligands to visualize vulnerability. The aim of this study was to explore the presence of activated macrophages in human atherosclerotic plaques by 99m Tc-folate imaging and to evaluate whether this technique can discriminate between an M1-like and M2-like macrophage phenotype. Methods: Carotid endarterect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…Thus, folate receptor positive macrophages have been shown to accumulate in inflamed lesions of patients with rheumatoid arthritis, Crohn's disease, atherosclerosis, osteoarthritis, Sjogren's syndrome, ischemia reperfusion injury, vasculitis, idiopathic pulmonary fibrosis, asthma, psoriasis and multiple sclerosis [31,[36][37][38][39][40][41][42], and these same sites of inflammation are characterized by increased vascular permeability due to the prominent release of such regulators of endothelial function as TNF-α [43], VEGF [44], histamine [45] and IL-2 [46]. By contrast, while solid tumors are often characterized by a leaky vasculature, their dense extracellular matrices and high cellular densities can strongly suppress NP permeation future science group Comparison of nanoparticle penetration into solid tumors & sites of inflammation Research Article beyond the capillary wall.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, folate receptor positive macrophages have been shown to accumulate in inflamed lesions of patients with rheumatoid arthritis, Crohn's disease, atherosclerosis, osteoarthritis, Sjogren's syndrome, ischemia reperfusion injury, vasculitis, idiopathic pulmonary fibrosis, asthma, psoriasis and multiple sclerosis [31,[36][37][38][39][40][41][42], and these same sites of inflammation are characterized by increased vascular permeability due to the prominent release of such regulators of endothelial function as TNF-α [43], VEGF [44], histamine [45] and IL-2 [46]. By contrast, while solid tumors are often characterized by a leaky vasculature, their dense extracellular matrices and high cellular densities can strongly suppress NP permeation future science group Comparison of nanoparticle penetration into solid tumors & sites of inflammation Research Article beyond the capillary wall.…”
Section: Resultsmentioning
confidence: 99%
“…Activated macrophages associated with tumors [40], asthma [42] and atherosclerosis [43] all express FR-β and regulatory M2 macrophage phenotypes [44]. M2 macrophages can be sub-divided into several subsets [45].…”
Section: Discussionmentioning
confidence: 99%
“…To date, most efforts for the development of ligands at FR2 receptors suitable for radio-imaging have been reported on SPECT tracers [126]. One report potentially interesting also for the analysis of cerebral microglia has been provided by Jager et al [126] Overexpression of FR2 in the prefrontal cortex of rats was demonstrated, recently, in a model of acute and chronic stress [48] in parallel with other M2 microglial markers.…”
Section: Potential Fr2 Ligands For Pet Tomographic Imagingmentioning
confidence: 99%